(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe knowledge and practice when a child has a fever and analyze some factors related to the handling of parents’ fever to take their children to Binh Duong General Hospital in 2019. Methods: Cross-sectional descriptive study on 445 parents taking children to the Pediatric Clinic, Binh Duong Hospital from December 2018 to April 2019, in the form of a face-to-face interview prepared. Results: 73.5% of parents had the right knowledge about the child’s temperature when having a fever, 68.1% had the right knowledge about the temperature to take medicine; 50.1% of parents know that fever is a beneficial factor for the child’s body and only 44.7% know that if a high fever will cause convulsions in children. 79.8% rate has the right knowledge about wiping cool for children. 24.7% know how to choose a fever-reducing medicine for a child, 45.6% practice the right way to consider the dose of a fever-reducing medicine based on the child’s weight and 78.7% of parents use antipyretics for children. children by mouth. 51.1% of parents complied with antibiotics prescribed by a doctor and 15.5% of the wrong practices were for children to use antibiotics when they had a fever.